Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1115/1.1289624
|View full text |Cite
|
Sign up to set email alerts
|

A Triaxial-Measurement Shear-Test Device for Soft Biological Tissues

Abstract: A novel shear-test device for soft biological tissue, capable of applying simple shear deformations simultaneously in two orthogonal directions while measuring the resulting forces generated in three axes, is described. We validated the device using a synthetic gel, the properties of which were ascertained from independent tensile and rotational shear tests. Material parameters for the gel were fitted using neo-Hookean analytical solutions to the independent test data, and these matched the results from the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 13 publications
0
53
0
Order By: Relevance
“…Viscoelastic material characterization can be best accomplished by varying loading histories over different modes of deformation since volume changes (bulk) and shape changes (shear) relate to different mechanisms of deformation 3 . Common modes of deformation used on soft tissues include: uniaxial compression/extension 17,[22][23][24][25] , shear 26,27 , indentation 6,8,10,12,[14][15][16] , torsion 5,28 , grasping 9 , and aspiration 29 . To characterize the time-dependent large strain response of soft tissues a few types of loading histories are most commonly used: creep response to a constant step load 14 , stress relaxation under a constant step displacement 9,15,19,25 , and constant strain rate ramp loading and unloading cycles 9,15,16,25 .…”
mentioning
confidence: 99%
“…Viscoelastic material characterization can be best accomplished by varying loading histories over different modes of deformation since volume changes (bulk) and shape changes (shear) relate to different mechanisms of deformation 3 . Common modes of deformation used on soft tissues include: uniaxial compression/extension 17,[22][23][24][25] , shear 26,27 , indentation 6,8,10,12,[14][15][16] , torsion 5,28 , grasping 9 , and aspiration 29 . To characterize the time-dependent large strain response of soft tissues a few types of loading histories are most commonly used: creep response to a constant step load 14 , stress relaxation under a constant step displacement 9,15,19,25 , and constant strain rate ramp loading and unloading cycles 9,15,16,25 .…”
mentioning
confidence: 99%
“…Similar results were observed at ω = 1.6, 2.0, and 2.5 rad/s (data are not shown here). The intra-cycle strain stiffening was also observed from gels of other biological molecules or tissues, including gluten gels [86] , fibrin gels [87] , actin filament network [41] , pedal mucus of snails [48] , bovine brain tissues [88] and myocardium isolated from rat heart septum [89] . Storm et al [90] reported the strain stiffening of various biological gels including actin, collagen, fibrin and vimentin.…”
Section: Linear Viscoelasticitymentioning
confidence: 94%
“…Equation (7) is the two-constant version of the energy function for the Mooney-Rivlin material (7) where C 1 and C 2 are material constants, and C 1 , C 2 > 0. The simplest polynomial based energy function is the neo-Hookean model (the case where C 2 = 0 in the Mooney-Rivlin model) and it is given by: (8) Ogden form of strain energy: Departing from the practice of writing the strain energy as a function of strain invariants I 1 and I 2 , Ogden 28 proposed a more general form of strain invariant for isotropic material, (9) where α is a real number, positive or negative. The Ogden form strain energy function can be written as: (10) where the C k 's are constants and k is the number of terms included in the summation.…”
Section: Hyperelastic Strain Energy Functions For Isotropic Incompresmentioning
confidence: 99%